2020
DOI: 10.1088/1757-899x/852/1/012144
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Road Accident Prediction Model along Federal Road FT050 Kluang-A/Hitam-B/Pahat Route Using Excess Zero Data

Abstract: Traffic accidents have become a major socio-economic problem in Malaysia as it is the primary cause of mortality. Over 60 percent of these fatal accidents occurred on rural roads. Nearly half of all fatalities took place on federal roads and over a quarter happened on state roads. It is also estimated that about 2 percent of the country’s Gross Domestic Product (GDP), or approximately RM 9 billion, is lost through road accidents. Previous studies managed to develop several models for modelling the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For example, the Poisson, NB, ZIP and ZINB were used to model of numbers of RAFs on the highest accident road F0050 in Malaysia [25] and in the Oromia region, Ethiopia [19]. Modeling zero inflated regression of Poisson and NB of the number of RTFs on the road F001 - Jalan Jb Air Hitam and on the road FT050 - Kluang-A/Hitam-B/Pahat, Malaysia was presented by [24] and [26], respectively. The results suggest that the zero inflated version models offered better statistical performance than the traditional models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Poisson, NB, ZIP and ZINB were used to model of numbers of RAFs on the highest accident road F0050 in Malaysia [25] and in the Oromia region, Ethiopia [19]. Modeling zero inflated regression of Poisson and NB of the number of RTFs on the road F001 - Jalan Jb Air Hitam and on the road FT050 - Kluang-A/Hitam-B/Pahat, Malaysia was presented by [24] and [26], respectively. The results suggest that the zero inflated version models offered better statistical performance than the traditional models.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the distribution of accidents, deaths, and injuries could be attributed to the variation between roads and their surroundings. Several studies estimate the frequency of RTAs and/or RAFs by traditional Poisson regression [17], Negative Binomial (NB) regression [18][19][20], and Conway-Maxwell Poisson (CMP) regression [21][22][23], as well as estimate the count data with excessive zeroes by zero-inflated regression models [24][25][26]. However, predictive models for deaths and/or injuries are limited in Thailand road safety.…”
Section: Introductionmentioning
confidence: 99%
“…ZIP and ZINB models can be effective at modeling data with excessive zeros since they allow for different sets of variables to model the zero state and the count state ( 14 ). The equations for the ZIP and ZINB models are the same as the equations for the Poisson model (Equation 2) and NB model (Equation 3), respectively, with the zero-inflated models having an additional model of the same form for the excess zero counts.…”
Section: Modeling Methodologiesmentioning
confidence: 99%
“…To address this issue, ZIP and ZINB models can be used for SPF development. These models allow for different sets of variables to model the zero state and the count state ( 14 ). A study conducted in Malaysia showed that a ZINB model outperformed Poisson and NB models as indicated by a lower Akaike information criterion (AIC) value ( 14 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Average Annual Daily Traffic (AADT) and speed of vehicles were used in the research for the traffic information [5]. In year of 2010, 2011, 2012 and 2013, the AADT was provide by the ministry of works Malaysia Highway planning unit road traffic volume Malaysia [6]. In this organization, it conducts a bi-monthly study at each year in a specific station in April for the first half data and in October for the other half year data [4].…”
Section: Traffic Informationmentioning
confidence: 99%